Proporción del diámetro mesio-distal de los dientes antero-superiores, como factor dimórfico sexual en un grupo de individuos mestizos colombianos. Estudio exploratorio - Acosta Chaparro, Dany Alejandra; Medina Lozano, Lizeth Natalia; Núñez Alonso, Cristian Camilo (Universidad Antonio Nariño, 2021)
The forensic dentistry is one of the most important tools for the identification of an anonymous individual, due to the capacity of the dental pieces to resist the change of shape and alterations as a result of their poor conservation.